STUDI ALTERNATIF PERENCANAAN STRUKTUR BAJA PADA BANGUNAN GEDUNG LAB TERPADU UNIVERSITAS ISLAM MALANG - Febri Renaldy; Warsito Warsito; Azizah Rachmawati (Universitas Islam Malang, 2020)
Steel structures are modern structural materials that are commonly used to build buildings and Bridges. As the changing ages with the growth of human resources increased especially thegrowing number of students, therefore the Islamic University of Malang built an integratedLaboratory. Steel construction is used because of easy installation and high strength. The integratedLaboratory Building of the Islamic University of Malang has a five floors, 40 meters of the lenght,16 meters of the widht and 20,6 meters of the height. In this final project a re-planning is carriedout using a stell frame structure. Re-planning this stell structure using the reference Standart ofplanning SNI 1726:2012, SNI 1727:2013, SNI 2847:2013, SNI 03-1726:2002 and SNI 03-17292002.Analysis of steel frame structure from integrated Laboratory calculation using 2D portalmodeling with STAAD Pro V8i application as well as planning the connection in each steel element,and in result a plate thickness of 12,5 centimeters using the principal reinforcement Ø10-125 ofprincipal reinforcement and Ø10-200 of stirrup reinforcement ; earthquake load is 3875,83 kg,7038,61 kg, 10355,5 kg, 13610,9 kg, 14821,2 kg ; joist uses 350.175.7.11 WF profile, 250.125.6.9WF, 200.100.5,5.8 WF ; main beam uses 900.300.16.28 profile WF ; the column uses 900.300.16.28profile WF. Pile foundation is used based on planning with a depth of up to 12 meters, with the SPTbased on the carrying capacity of the pile is 110,319 tons.Keywords : Altenative studies, Planning, Structure, Steel, Building